Development and physicochemical characterization of solid dispersions containing praziquantel for the treatment of schistosomiasis - Dametto, P. R.; Dametto, A. C. [UNESP]; Polese, L. [UNESP]; Ribeiro, C. A. [UNESP]; Chorilli, M. [UNESP]; de Freitas, Osvaldo (Springer Nature, 2017)
Praziquantel (PZQ) is an anthelminthic agent active against parasitic flatworms of the Schistosoma type and the most important drug for the treatment and morbidity control of schistosomiasis. In this study, a high-performance liquid chromatography method was employed for quantification of PZQ in the physical mix (PM) and solid dispersion (SD) prepared by Fusion Method utilizing the carriers Gelucire® 50/13 and mannitol in ratio 3:1; 1:1; 1:3 PZQ/carrier. Furthermore, PM and SD were characterized by Thermogravimetry–Differential Thermal Analysis, Differential Scanning Calorimetry, Infrared Spectroscopy, X-Ray Diffraction, and Scanning Electron Microscopy. Solubility assay was made to evaluate the solubility of PZQ in purified water, in 0.1 mol L−1 HCl solution and 0.2 mol L−1 buffered phosphate solution. PZQ dissolution test was carried out in 0.1 mol L−1 HCl and 0.2 M buffered phosphate (pH 6.8). The interaction between PZQ and carriers in PMs and SDs was evidenced due to experimental enthalpy, which was different from expected enthalpy. However, this interaction did not affect the solubility of the drug. In PZQ dissolution test, the best result was for SD 1:1 PZQ/Gelucire, which presented higher dissolution rate and release extension than PM and PZQ. Thus, SD may be a strategy to enhance the solubility and dissolution, a crucial step in the development of a pharmaceutical dosage form containing PZQ for possible application in the treatment of schistosomiasis.
Keywords: HPLC–UV; Physical mix; Praziquantel; Solid dispersion